ASSOCIATION OF BILATERAL RADIOULNAR SYNOSTOSIS WITH OSTEOGENESIS IMPERFECTA TYPE 1 - CASE PRESENTATION - Valeriu V. Lupu; Mirabela Subotnicu; Ancuța Ignat; Gabriela Păduraru; Irina Naumcieff; Bogdan Ciubară; Marin Burlea (Romanian Society of Oral Rehabilitation, 2016)
Osteogenesis imperfecta (OI) is a group of rare congenital conditions characterized mainly by bone brittleness secondary to mutations in the genes encoding collagen. The medical history together with a clinical examination in detail of the fractures is highly important in directing the diagnosis towards OI. The authors present an OI case diagnosed in an 11-years old patient with a history of multiple fractures, with bone deformations, which associates a rare congenital malformation - bilateral radioulnar synostosis. This case needs multidisciplinary monitoring (pediatric, orthopaedic, genetic, psychologic).